Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/nrclinonc.2015.234
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Modern approaches to HLA-haploidentical blood or marrow transplantation.

Abstract: Allogeneic blood or bone-marrow transplantation (alloBMT) is a potentially curative treatment for a variety of haematological malignancies and nonmalignant diseases. Historically, human leukocyte antigen (HLA)-matched siblings have been the preferred source of donor cells owing to superior outcomes compared with alloBMT using other donors. Although only approximately onethird of patients have an HLA-matched sibling, nearly all patients have HLA-haploidentical related donors. Early studies using HLA-haploidenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…Even though PTCy is broadly and highly effective in preventing chronic GvHD in patients undergoing alloBMT, 1,2,46 our study has not revealed any factor that can prognosticate which of our patients will still develop chronic GvHD despite PTCy treatment. It is possible that the lack of any significant findings was due in part to the low incidence of chronic GvHD in our patients and thus low statistical power to detect true differences that may exist; however, the number of chronic GvHD events (n=24) was identical to the number of NRM events (n=24) and more than the number of grade III–IV acute GvHD events (n=18).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Even though PTCy is broadly and highly effective in preventing chronic GvHD in patients undergoing alloBMT, 1,2,46 our study has not revealed any factor that can prognosticate which of our patients will still develop chronic GvHD despite PTCy treatment. It is possible that the lack of any significant findings was due in part to the low incidence of chronic GvHD in our patients and thus low statistical power to detect true differences that may exist; however, the number of chronic GvHD events (n=24) was identical to the number of NRM events (n=24) and more than the number of grade III–IV acute GvHD events (n=18).…”
Section: Discussionmentioning
confidence: 61%
“…1 This approach has facilitated the safe performance of T-cell-replete human leukocyte antigen (HLA)-haploidentical alloBMT 13 and can function as single-agent GvHD prophylaxis after myeloablative conditioning and HLA-matched bone marrow allografting. 1,46 Despite these clinical successes with low rates of severe acute GvHD, chronic GvHD, and non-relapse mortality (NRM), biomarkers prognostic for GvHD or predictive for NRM occurring despite the use of PTCy have not been explored. Such biomarkers could potentially help guide treatment decisions and direct more intensive clinical surveillance of patients at high-risk for poor outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is interesting because the outcomes with haplo-matched family donors are gradually improving, with some studies reporting outcomes similar to those with matched unrelated donors for haplo-HSCT [9]. The best haplo-HSCT results are being reported in AML patients, with results similar to those of allo-HSCT from matched sibling donors [1011].…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic HSCT (allo-HSCT) has curative potential essentially through the immune-mediated graft-versus-leukemia (GvL) effect [16]. In contrast to total-body irradiation or chemotherapies, the immune effectors also eradicate malignant stem cells, thus minimizing the risk for disease relapse.…”
Section: Nk Cells and Hematopoietic Stem Cell Transplantation For Leumentioning
confidence: 99%